Relationship between Total Phosphorus and Chloropyll-a in the PLTA Koto Panjang Reservoir in Batu Bersurat village, XIII Koto Kampar Districts, Kampar Regency, Riau Province - Nitami S.M Sihombing; Tengku Dahril; Madju Siagian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract Several activities in the PLTA Koto Panjang Reservoir in Batu Bersurat, have provided organic and inorganic inputs to the waters, with increased phosphate concentrations and have influenced phytoplankton growth and chlorophyll-a concentrations in the waters. This research  aims  to  understand the relationship between Total P and Chloropyll-a in the PLTA Koto Panjang Reservoir in Batu Bersurat village and it was conducted in June-July 2019. Sampling was determined at 3 locations namely Station I (KJA area), Station II (areas which are not much affected by activities) and Station III (Tourism and plantation areas). Each station has 3 sampling points namely surface, in 2 Secchi depthand in 4 Secchi depth. Sampling was carried out 4 times with a time interval of a week. Water quality parameters measured in this study are Total P, Chlorophyll-a, Nitrate, Transparency, Temperature, pH, Dissolved Oxygen and free carbon dioxide. The water quality parameter values were as follows: total phosphorus 0,205-0,247 mg/L, chlorophyll-a4,65-6,17 µg/L, dissolved oxygen 6,35-6,88 mg/L, free carbon dioxide 5-12,99 mg/L, temperature 29-31 oC, transparency 145,1-187,5 cm, pH 5-6,25 dan nitrate 0,06-0,08 mg/L. Relationship between total phosphorus with Chlorophyll-a retrieved value r of 0,7023-0,7643. Based on the correlation coefficient, the relationship of total phosphorus with Chlorophyll-a in PLTA Koto Panjang Reservoir in Batu Bersurat village in power (non linier) is strongly. Keywords: Total phosphorus; Chlorophyll-a, Reservoir Puddles, depth